2017
DOI: 10.1007/s00442-017-4039-5
|View full text |Cite
|
Sign up to set email alerts
|

Belowground competition drives invasive plant impact on native species regardless of nitrogen availability

Abstract: Plant invasions and eutrophication are pervasive drivers of global change that cause biodiversity loss. Yet, how invasive plant impacts on native species, and the mechanisms underpinning these impacts, vary in relation to increasing nitrogen (N) availability remains unclear. Competition is often invoked as a likely mechanism, but the relative importance of the above and belowground components of this is poorly understood, particularly under differing levels of N availability. To help resolve these issues, we q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 68 publications
0
42
1
Order By: Relevance
“…Furthermore, we are unable to rule out effects of belowground competition, as this study only included the assessment of aboveground biomass. An experiment using the grass species Agrostis capillaris , for example, showed that the negative effect of this invasive species on the native vegetation was driven by belowground competition (Broadbent, Stevens, Peltzer, Ostle, & Orwin, ). Interestingly, the authors found this effect regardless of N availability.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we are unable to rule out effects of belowground competition, as this study only included the assessment of aboveground biomass. An experiment using the grass species Agrostis capillaris , for example, showed that the negative effect of this invasive species on the native vegetation was driven by belowground competition (Broadbent, Stevens, Peltzer, Ostle, & Orwin, ). Interestingly, the authors found this effect regardless of N availability.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors, such as disturbance and priority effects, i.e. where the first species to arrive following a disturbance ultimately dominates the community (Seabloom et al 2003), or superior competitive abilities (Sun et al 2014;Broadbent et al 2017), likely underlie the invasions of other grass species, including A. capillaris and A. odoratum. In combination with findings from previous studies, our results suggest that predicting which invasive plant species are most likely to benefit from belowground enemy release will be difficult, due to large variation within functional groups and across different habitats in the introduced range.…”
Section: Discussionmentioning
confidence: 99%
“…A recent paper by Broadbent et al . 13 highlighted the potential importance of root competition in the interactions between invasive and native grasses in New Zealand. This small-scale study only investigated the relationship between three species but demonstrated the importance of belowground competition, a mechanism that has received very little attention, in driving their interactions and highlights this as an area in need of future research.…”
Section: Threats To Grasslandsmentioning
confidence: 99%